Broadband meter‐wavelength observations of ionospheric scintillation. Issue 12 (19th December 2014) - Fallows, R. A.; Coles, W. A.; McKay‐Bukowski, D.; Vierinen, J.; Virtanen, I. I.; Postila, M.; Ulich, Th.; Enell, C‐F.; Kero, A.; Iinatti, T.; Lehtinen, M.; Orispää, M.; et al.
Abstract: Intensity scintillations of cosmic radio sources are used to study astrophysical plasmas like the ionosphere, the solar wind, and the interstellar medium. Normally, these observations are relatively narrow band. With Low‐Frequency Array (LOFAR) technology at the Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA) station in northern Finland we have observed scintillations over a three‐octave bandwidth. "Parabolic arcs, " which were discovered in interstellar scintillations of pulsars, can provide precise estimates of the distance and velocity of the scattering plasma. Here we report the first observations of such arcs in the ionosphere and the first broadband observations of arcs anywhere, raising hopes that study of the phenomenon may similarly improve the analysis of ionospheric scintillations. These observations were made of the strong natural radio source Cygnus‐A and covered the entire 30–250 MHz band of KAIRA. Well‐defined parabolic arcs were seen early in the observations, before transit, and disappeared after transit although scintillations continued to be obvious during the entire observation. We show that this can be attributed to the structure of Cygnus‐A. Initial results from modeling these scintillation arcs are consistent with simultaneous ionospheric soundings taken with other instruments and indicate that scattering is most likely to be associated more with the topside ionosphere than the F region peak altitude. Further modeling and possible extension to interferometric observations, using international LOFAR stations, are discussed. Key Points: First multioctave low‐frequency observations of ionospheric scintillation Probe ionospheric scintillation velocities and scattering altitudes